2022
DOI: 10.1111/ajt.16874
|View full text |Cite
|
Sign up to set email alerts
|

Capitalizing on the concept of local immune suppression by inhalation for lung transplant recipients

Abstract: A placebo‐controlled randomized‐trial marked by limited enrollment and early trial termination shows that inhaled cyclosporine, when added to systemic immune suppression for lung transplant recipients, was safe and improved early‐in‐trial clinical parameters of bronchiolitis obliterans syndrome. See Kneidinger et al. (page 222).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In the case of a nebulisation product, a CsA solution using propylene glycol as a solvent [ 14 ] or a liposomal formulation has been proposed to increase the pulmonary exposure of the drug. Despite the good performance in clinical trials, the CsA solution for nebulisation did not reach the market, perhaps because of the possible irritant effect of the solvent used [ 37 , 38 ]. Other clinical trials conducted using inhaled liposomal CsA demonstrated the capability of the drug to increase BOS-free survival [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of a nebulisation product, a CsA solution using propylene glycol as a solvent [ 14 ] or a liposomal formulation has been proposed to increase the pulmonary exposure of the drug. Despite the good performance in clinical trials, the CsA solution for nebulisation did not reach the market, perhaps because of the possible irritant effect of the solvent used [ 37 , 38 ]. Other clinical trials conducted using inhaled liposomal CsA demonstrated the capability of the drug to increase BOS-free survival [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%